2014
DOI: 10.3109/02770903.2014.906606
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled breath temperature in children: reproducibility and influencing factors

Abstract: Measurements of exhaled breath temperature are highly reproducible, yet influenced by several factors. Corrected values, i.e. normalized exhaled breath temperature, could help us to assess the effect of therapy with inhaled corticosteroids. More studies are needed to improve the usefulness of the exhaled breath temperature measured with the tidal breathing technique in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…In all those three situations the values in expiration were higher than in inspiration. This fact is concurrent with the literature, since during expiration the warm air from the lungs is exhaled, thus warming the nose and mouth, while during inspiration there is cooling of the nasal vestibule and mouth (8,9) . As expected, there were no differences in the temperatures of the mouth during nasal breathing, since there was no air ow through the mouth, and all participants had their lips sealed, so thermography was effective in detecting temperature changes during breathing.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In all those three situations the values in expiration were higher than in inspiration. This fact is concurrent with the literature, since during expiration the warm air from the lungs is exhaled, thus warming the nose and mouth, while during inspiration there is cooling of the nasal vestibule and mouth (8,9) . As expected, there were no differences in the temperatures of the mouth during nasal breathing, since there was no air ow through the mouth, and all participants had their lips sealed, so thermography was effective in detecting temperature changes during breathing.…”
Section: Discussionsupporting
confidence: 74%
“…Studies have employed thermography in the evaluation of breathing, mainly using it as a technique to quantify the respiratory ow or rate (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) . A recent study also aimed to determine nasal functionality by means of this method and obtained promising results (5) .…”
Section: Introductionmentioning
confidence: 99%
“…Our study has other strengths: we have adjusted our analysis for baseline EBT, which is of particular relevance given the high dependence to ∆EBT. Also, recent studies have highlighted several factors influence EBT and we have addressed that question also. We have shown that central temperature significantly influences ∆EBT in elite swimmers, and we have analyzed the possible confounding effect of several demographic variables and training characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Thermography has proven to be an important tool in investigating respiratory function. Promising studies have been based on the premise that the temperature around the nostrils fluctuates throughout the respiratory cycle (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) . During inspiration, cold air from the environment is inhaled, while during expiration, warm air from the lungs is exhaled (9)(10)(11) .…”
Section: Introductionmentioning
confidence: 99%
“…Promising studies have been based on the premise that the temperature around the nostrils fluctuates throughout the respiratory cycle (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) . During inspiration, cold air from the environment is inhaled, while during expiration, warm air from the lungs is exhaled (9)(10)(11) . Thermograms are then capable of identifying such changes and representing qualitatively and quantitatively the temperature variation around the nasal vestibule.…”
Section: Introductionmentioning
confidence: 99%